The Effect of Varieties and Fungicide Spray Frequencies on Septoria Leaf Blotch (Mycosphaerella graminicola) Epidemics on Bread Wheat in Western Amhara, Ethiopia - Alamirew, Belayneh; Badebo, Ayele; Abera, Merkuz (International Journal of Sustainable Agricultural Research, 2019)
Bread wheat (Triticum aestivum L.) is one of the most important small grain cereals produced worldwide. Despite its economic significance, wheat production and productivity is challenged by biotic and abiotic factors. Septoria leaf blotch (Mycosphaerella graminicola), is among the most important pathogens that inflict qualitative and quantitative losses on susceptible wheat varieties in the Ethiopian highlands. A field experiment was conducted at Adet and Debre Tabor, three frequencies of fungicide (propiconazole, Tilt 250 EC) plus check and three varieties (Alidoro, Danda’a and Gambo) were used. The experiment was laid out in a randomized complete block design (RCBD) in factorial arrangement with three replications. SLB disease development was quite high at Debre Tabor compared to Adet. At Debre Tabor, the maximum SLB severity (78.8%) was noted on variety Gambo followed by Danda’a (70.3%) whereas 46.09% and 37.44% severities noted on these varieties at Adet, respectively. At Debre Tabor the highest sAUDPC (44.35%days and 39.8 %days), disease progress rate (0.019402 and 0.035895 unit/day) on all and flag leaves, respectively. The highest Septoria progress coefficient was noted from the unsprayed plot of Gambo (0.76). Based on the results, a single fungicide spray (Tilt 250EC) for Alidoro and Danda’a (moderately resistant and moderately susceptible) could minimize the epidemics of SLB. But for Gambo (susceptible variety) two fungicide spray reduces the progress and development of SLB. Timely application of efficient systemic fungicides could reduce the epidemics of the pathogen. However, other cultural methods could be further study for the epidemics of this particular pathogen.